Arachidonic acid enhances reproduction in Daphnia magna and mitigates changes in sex ratios induced by pyriproxyfen. (21st January 2015) - Ginjupalli, Gautam K.; Gerard, Patrick D.; Baldwin, William S.
Abstract Arachidonic acid is 1 of only 2 unsaturated fatty acids retained in the ovaries of crustaceans and an inhibitor of HR97g, a nuclear receptor expressed in adult ovaries. The authors hypothesized that, as a key fatty acid, arachidonic acid may be associated with reproduction and potentially environmental sex determination in Daphnia. Reproduction assays with arachidonic acid indicate that it alters female:male sex ratios by increasing female production. This reproductive effect only occurred during a restricted Pseudokirchneriella subcapitata diet. Next, the authors tested whether enriching a poorer algal diet (Chlorella vulgaris) with arachidonic acid enhances overall reproduction and sex ratios. Arachidonic acid enrichment of a C. vulgaris diet also enhances fecundity at 1.0 µM and 4.0 µM by 30% to 40% in the presence and absence of pyriproxyfen. This indicates that arachidonic acid is crucial in reproduction regardless of environmental sex determination. Furthermore, the data indicate that P. subcapitata may provide a threshold concentration of arachidonic acid needed for reproduction. Diet‐switch experiments from P. subcapitata to C. vulgaris mitigate some, but not all, of arachidonic acid's effects when compared with a C. vulgaris–only diet, suggesting that some arachidonic acid provided by P. subcapitata is retained. In summary, arachidonic acid supplementation increases reproduction and represses pyriproxyfen‐induced environmental sex determination in D. magna in restricted diets. A diet rich in arachidonic acid may provide protection from some reproductive toxicants such as the juvenile hormone agonist pyriproxyfen. Environ Toxicol Chem 2015;34:527–535. © 2014 SETAC